Integrated risk assessment framework for mixed use real estate development: Retail–office configuration - Jessy Jessy Mercy Paul; Dr. Abhijit Rastogi (International Journal of Rural and Regional Development, 2024)
Mixed-use real estate development is a multifaceted challenge that offers significant potential benefits, yet developers and urban planners face skepticism and uncertainty. Despite the promise of enhancing property values, promoting secure neighborhoods, stimulating economic vitality, and creating synergies, the associated risks demand a critical examination. This research seeks to address this gap by constructing a comprehensive risk assessment framework for mixed-use real estate projects. The literature review underscores the substantial advantages of mixed-use buildings and developments, highlighting their positive impact on the broader real estate landscape. Recognizing the importance of investment strategies in real estate, the study delves into various factors influencing the sector. The primary objective is to identify, correlate, rank, and assess risk variables, providing valuable insights to guide decision-making and enhance risk management practices specifically tailored to mixed-use real estate projects. Through the analysis of these risk factors, the research contributes a multifaceted framework that empowers stakeholders to prioritize efforts and allocate resources effectively. The conclusion underscores that the success of mixed-use projects in India relies on a profound understanding of local dynamics, adherence to regulatory requirements, tailored tenant management, strategic positioning, financial prudence, and seamless technological integration. This integrated risk assessment framework serves as a valuable tool for navigating the complexities of mixed-use real estate development, fostering sustainable success in the Indian context. By addressing skepticism among developers and urban planners, the research aims to bridge the gap between the potential benefits of mixed-use projects and the apprehensions surrounding their implementation. Ultimately, the framework provides a structured approach to mitigating risks, facilitating informed decision-making, and maximizing the positive impact of mixed-use real estate projects on the Indian real estate landscape.
Keywords: Framework; Mixed use development; Risk assessment; real estate; risk